A Qualitative Study on Experience of Stigma and Discrimination in Health Care Sector Among PLHA Attending VCTC Of New Civil Hospital and GSNP+ Of Surat - Bharat H Patel; Ratan K Srivastava; Rashmi Sharma; Mohua Moitra (Medsci Publications, 2016)
Introduction: Within health care settings, HIV-related stigma is a recognized barrier to access of HIV prevention and treatment services. The current study was undertaken with the objective to study various forms of stigma and discrimination towards PLHA in health care sector. Methods: Total 30 PLHA were selected from VCTC of tertiary care hospital and GSNP+ in Surat city. Information on stigma and discrimination gathered through in-depth interview. Results: Stigma and/or discrimination were experienced by 36.7% respondents and 13.3% experienced harassment from health care staff. As per 13.3% respondents, they were charged extra by private practitioners. Change of treatment modality from invasive to oral was observed by 13.3% respondents. Practice of taking extra precautions while treating PLHA was experienced by 44.4% respondents. Due to fear of stigma and/or discrimination from health care staff, 26.7% respondents were hiding their status while seeking medical care and 16.7% were avoiding doctor/hospital, and taking the drugs over counter for minor illnesses. Conclusion: Present study concluding that various forms of stigma and discrimination do exist in health care sector towards PLHA. Although stigma is a pervasive and daunting problem in the health care setting, much can be done to address its causes and consequences.